CONSIDERATIONS ON INFORMAL LEARNING: DIFFERENT CONCEPTS AND THEIR DIMENSIONS - Bagdonaite-Stelmokiene, Ramune; Zydziunaite, Vilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The definition of “informal learning” is ambiguous and thus distinguished by the diverse interpretations. The article aims to reveal identical learning dimensions (process, activity, context, interactions and outcomes), which set up different concepts of “informal learning”. The research question refers to the content of dimensions for distinct concepts of “informal learning”. The analysis has disclosed the “informal learning” to be continuum between “self-directed learning”, “self-regulated learning”, “self-managed learning”, “experiential learning”, “incidental/accidental learning”, “situated learning”, “learning through socialization” or “tacit learning”. Those diverse types of “informal learning” supplement each other rather than compete against. Learning intention, process and context setting might be manifested in distinct degrees, however, “informal learning” may refer to the construct covering learning forms, activities and acquired learning outcomes supplementing each other.